Law-enforcement of customs authorities in the UkrSSR during the NEP - Chamlay, Vitaliy (Skhid, 2013)
In the noted article author, on the basis of analysis of a spring base and scientific labours of leading specialists on history and right lights up the problems of reformation of the law-enforcement system and value of custom organs at a fight against criminality in Ukraine to the period of NEP.